Integrated Analysis of circRNA-miRNA-mRNA Regulatory Networks in the Intestine of Sebastes schlegelii Following Edwardsiella tarda Challenge - Cao, Min; Yan, Xu; Su, Baofeng; Yang, Ning; Fu, Qiang; Xue, Ting; Song, Lin; Li, Qi; Li, Chao (Frontiers in Immunology, 2021)
Sebastes schlegelii, an important aquaculture species, has been widely cultured in East Asian countries. With the increase in the cultivation scale, various diseases have become major threats to the industry. Evidence has shown that non-coding RNAs (ncRNAs) have remarkable functions in the interactions between pathogens and their hosts. However, little is known about the mechanisms of circular RNAs (circRNAs) and coding RNAs in the process of preventing pathogen infection in the intestine in teleosts. In this study, we aimed to uncover the global landscape of mRNAs, circRNAs, and microRNAs (miRNAs) in response to Edwardsiella tarda infection at different time points (0, 2, 6, 12, and 24 h) and to construct regulatory networks for exploring the immune regulatory mechanism in the intestine of S. schlegelii. In total, 1,794 mRNAs, 87 circRNAs, and 79 miRNAs were differentially expressed. The differentially expressed RNAs were quantitatively validated using qRT-PCR. Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis showed that most of the differentially expressed mRNA genes and the target genes of ncRNAs were related to immune signaling pathways, such as the NF-κB signal pathway, pathogen recognition receptors related to signaling pathways (Toll-like receptors and Nod-like receptors), and the chemokine signaling pathway. Based on these differentially expressed genes, 624 circRNA-miRNA pairs and 2,694 miRNA-mRNA pairs were predicted using the miRanda software. Integrated analyses generated 25 circRNA-miRNA-mRNA interaction networks. In a novel_circ_0004195/novel-530/IκB interaction network, novel_530 was upregulated, while its two targets, novel_circ_0004195 and IκB, were downregulated after E. tarda infection. In addition, two circRNA-miRNA-mRNA networks related to apoptosis (novel_circ_0003210/novel_152/apoptosis-stimulating of p53 protein 1) and interleukin (novel_circ_0001907/novel_127/interleukin-1 receptor type 2) were also identified in our study. We thus speculated that the downstream NF-κB signaling pathway, p53 signaling pathway, and apoptosis pathway might play vital roles in the immune response in the intestine of S. schlegelii. This study revealed a landscape of RNAs in the intestine of S. schlegelii during E. tarda infection and provided clues for further study on the immune mechanisms and signaling networks based on the circRNA-miRNA-mRNA axis in S. schlegelii.